The cost‐effectiveness of universal late‐pregnancy screening for macrosomia in nulliparous women: a decision analysis. (5th June 2019) - Wastlund, D; Moraitis, AA; Thornton, JG; Sanders, J; White, IR; Brocklehurst, P; Smith, GCS; Wilson, ECF
Abstract : Objective: To identify the most cost‐effective policy for detection and management of fetal macrosomia in late‐stage pregnancy. Design: Health economic simulation model. Setting: All English NHS antenatal services. Population: Nulliparous women in the third trimester treated within the UK NHS. Methods: A health economic simulation model was used to compare long‐term maternal–fetal health and cost outcomes for two detection strategies (universal ultrasound scanning at approximately 36 weeks of gestation versus selective ultrasound scanning), combined with three management strategies (planned caesarean section versus induction of labour versus expectant management) of suspected fetal macrosomia. Probabilities, costs and health outcomes were taken from literature. Main outcome measures: Expected costs to the NHS and quality‐adjusted life‐years (QALYs) gained from each strategy, calculation of net benefit and hence identification of most cost‐effective strategy. Results: Compared with selective ultrasound, universal ultrasound increased QALYs by 0.0038 (95% CI 0.0012–0.0076), but also costs by £123.50 (95% CI 99.6–149.9). Overall, the health gains were too small to justify the cost increase given current UK thresholds cost‐effective policy was selective ultrasound coupled with induction of labour where macrosomia was suspected. Conclusions: The most cost‐effective policy for detection and management of fetal macrosomia is selective ultrasound scanning coupled with induction of labour for all suspected cases of macrosomia. Universal ultrasound scanning for macrosomia in late‐stage pregnancy is not cost‐effective. Tweetable abstract: Universal late‐pregnancy ultrasound screening for fetal macrosomia is not warranted. Tweetable abstract: Universal late‐pregnancy ultrasound screening for fetal macrosomia is not warranted.